Ischemic Postconditioning Regulates New Cell Death Mechanisms in Stroke: Disulfidptosis - Shanpeng Liu; Qike Wu; Can Xu; Liping Wang; Jialing Wang; Cuiying Liu; Heng Zhao (Biomolecules)
Background and Objective: Stroke poses a critical health issue without effective neuroprotection. We explore ischemic postconditioning’s (IPostC) potential to mitigate stroke-induced brain injury, focusing on its interaction with disulfidptosis, a novel cell death pathway marked by protein disulfide accumulation. We aim to clarify IPostC’s protective mechanisms against stroke through gene sequencing and experimental analysis in mice. Methods: Through our initial investigation, we identified 27 disulfidptosis-related genes (DRGs) and uncovered their interactions. Additionally, differential gene analysis revealed 11 potential candidate genes that are linked to disulfidptosis, stroke, and IPostC. Our comprehensive study employed various analytical approaches, including machine learning, functional enrichment analysis, immune analysis, drug sensitivity analysis, and qPCR experiments, to gain insights into the molecular mechanisms underlying these processes. Results: Our study identified and expanded the list of disulfidptosis-related genes (DRGs) critical to stroke, revealing key genes and their interactions. Through bioinformatics analyses, including PCA, UMAP, and differential gene expression, we were able to differentiate the effects of stroke from those of postconditioning, identifying Peroxiredoxin 1 (PRDX1) as a key gene of interest. GSEA highlighted PRDX1’s involvement in protective pathways against ischemic damage, while its correlations with various proteins suggest a broad impact on stroke pathology. Constructing a ceRNA network and analyzing drug sensitivities, we explored PRDX1’s regulatory mechanisms, proposing novel therapeutic avenues. Additionally, our immune infiltration analysis linked PRDX1 to key immune cells, underscoring its dual role in stroke progression and recovery. PRDX1 is identified as a key target in ischemic stroke based on colocalization analysis, which revealed that PRDX1 and ischemic stroke share the causal variant rs17522918. The causal relationship between PRDX1-related methylation sites (cg02631906 and cg08483560) and the risk of ischemic stroke further validates PRDX1 as a crucial target. Conclusions: These results suggest that the DRGs are interconnected with various cell death pathways and immune processes, potentially contributing to IPostC regulating cell death mechanisms in stroke.